Soil genesis, classification and soil-crop suitability of Serdang and Malacca soil series in a Malaysian public university - Aliyu, Santuraki Hassan (2017)
A study was conducted to update the soil data of Serdang and Malacca Series. The soil data update was conducted in order to obtain comprehensive soil data for characterization of physical, chemical and mineralogical properties of Serdang Series (Ultisols Order) and Malacca Series (Oxisols Order) and within UPM campus area. The soil data were used for Soil-Crop Suitability assessment as stated by Wong (2009) and FAO Land Evaluation (1976) that benefits farmers, soil scientist and to some extent, benefits stakeholders in future soil studies. A total of four soil profiles were dug that, represent Serdang and Malacca Series. For each soil series, the soil profile represent two condition, which are minimal disturbance and highly disturbed soil condition. Following the soil profile preparation, the soil classification was conducted based on USDA Soil Taxonomy (Soil Survey Staff, 2014).